2011
DOI: 10.1017/s0033291711002108
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic-like experiences in a community sample of 8000 children aged 9 to 11 years: an item response theory analysis

Abstract: Assessing PLEs during middle childhood is feasible and supplements information concerning internalizing and externalizing problems presented by children. The hallucination-like experiences constitute appropriate items to screen the population to identify children who may require further clinical assessment or monitoring. Longitudinal follow-up of the children is required to determine sensitivity and specificity of the PLE items for later psychotic illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
175
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(187 citation statements)
references
References 47 publications
10
175
2
Order By: Relevance
“…Subclinical psychotic symptoms or psychotic-like experiences (PLEs) in childhood and adolescence are associated with concurrent emotional and behavioural difficulties (Laurens et al, 2007(Laurens et al, , 2012Nishida et al, 2008;Scott et al, 2009;Armando et al, 2010;Bartels-Velthuis et al, 2010;Polanczyk et al, 2010;Barragan et al, 2011;Kelleher et al, 2012b). PLEs that persist into adulthood increase risk for social dysfunction (Rossler et al, 2007), affective disturbance (van Rossum et al, 2011), substance misuse (Dhossche et al, 2002), and psychotic disorder .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subclinical psychotic symptoms or psychotic-like experiences (PLEs) in childhood and adolescence are associated with concurrent emotional and behavioural difficulties (Laurens et al, 2007(Laurens et al, , 2012Nishida et al, 2008;Scott et al, 2009;Armando et al, 2010;Bartels-Velthuis et al, 2010;Polanczyk et al, 2010;Barragan et al, 2011;Kelleher et al, 2012b). PLEs that persist into adulthood increase risk for social dysfunction (Rossler et al, 2007), affective disturbance (van Rossum et al, 2011), substance misuse (Dhossche et al, 2002), and psychotic disorder .…”
Section: Introductionmentioning
confidence: 99%
“…PLEs prior to adolescence may constitute part of a spectrum of normative development (Laurens et al, 2012). Longitudinal studies following adolescents into adulthood distinguish short-lived or transitory PLEs that may be relatively benign from persistent PLEs that impose a greater likelihood of concurrent, and later, psychiatric morbidity and social impairment (Cougnard et al, 2007;Woods et al, 2009;Dominguez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much research has established that psychotic experiences have a higher prevalence in the general population than psychotic disorders [1][2][3][4]. A meta-analysis of all community studies of psychotic experiences in children and adolescents found a median population prevalence of 17% in children aged 9-12 years and 7.5% in those aged 13-18 years [5].…”
Section: Introductionmentioning
confidence: 99%